A natureza da ciência e o erro: reflexões sobre o conto “ótima é a água” por alunos de ensino médio - Cedran, Débora Piai; Lino, Alex; Neves, Marcos Cesar Danhoni; Kiouranis, Neide Maria Michellan (Góndola, enseñanza y aprendizaje de las ciencias, 2017)
This paper presents results of a study that aimed to analyze conceptions of science, scientist's profile and scientific development of High School's students through activities based on the so-called short story "Excellent is the Water” by Primo Levi. Its contents promote discussions about the importance of breaking the empirical-inductive view of science as well as the importance of error in scientific development. Bachelard's epistemology guided the study using as a data collection instrument a questionnaire with open questions answered by students at the end of the activity. The main contribution of this study relates to generating reflections and contradictions and, understanding the importance of error in constructions of science and scientific development.